Integrating Multidisciplinary Approaches into Legal Education Through Contemporary Air Law Case Studies - Rafika Rizky Aulia Rahman; Dinda Anna Zatika; Reisa Malida; Nabila Firstia Izzati; Adam Muhammad Yanis (Jurnal Pengabdian Cita Masyarakat, 2026)
Technological advancements and globalization transform legal issues into increasingly complex and cross sectoral matters; however, legal education frequently remains entangled in fragmented approaches. This community outreach initiative aims to enhance student awareness regarding the significance of multidisciplinary perspectives in comprehending contemporary legal dynamics through air law case studies. Air law was selected due to its inherently intersecting nature across various regimes, encompassing civil, criminal, administrative, international, and technological law. The implementation method was conducted via interactive workshops involving initial perception measurements, material delivery based on andragogy, and air taxi case analysis simulations. Outcomes indicate a paradigm shift among participants, transitioning from sectoral thinking tendencies toward the capability to identify interconnected legal dimensions within concrete events. Final evaluations demonstrate that this problem based learning intervention effectively broadens students legal reasoning scope for future professional challenges. Integrating innovative case studies serves as a catalyst in deconstructing linear mindsets toward an integrative understanding.